2023
DOI: 10.1108/jiabr-09-2021-0240
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Shari’ah supervisory board and the performance of Islamic banks: evidence from an emerging economy of Pakistan

Abstract: Purpose Given the relative importance of the Shari’ah supervisory boards (SSBs) in Islamic banks’ (IBs’) performance, this study aims to examine the impact of SSB diversity on IBs’ performance from the stakeholders’ perspective in the context of Pakistan. Design/methodology/approach Random-effects model and generalized method of moment are used to investigate the impact of SSB diversity on IBs’ performance across a panel data of 22 Islamic banks in Pakistan from 2005 to 2020 inclusive. Findings The finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…Research conducted by Mayur & Saravanan (2017) revealed that the number of boards that are too high could cause a bank's performance to decrease. The effect of board size on bank performance is also stated by Khan et al (2023) who state that board size influences the success of Islamic banks in Pakistan.…”
Section: Previous Study and Hypothesis Corporate Governancementioning
confidence: 90%
“…Research conducted by Mayur & Saravanan (2017) revealed that the number of boards that are too high could cause a bank's performance to decrease. The effect of board size on bank performance is also stated by Khan et al (2023) who state that board size influences the success of Islamic banks in Pakistan.…”
Section: Previous Study and Hypothesis Corporate Governancementioning
confidence: 90%
“…SSB qualifications are important for decision-making. Empirical research implies that diverse educational backgrounds are linked to different social status, networking and professional development paths (Khan et al, 2023). Heterogeneity in educational background provides SSB with different perspectives and cognitive paradigms that affect vocational development and social contacts.…”
Section: Imefm 173mentioning
confidence: 99%
“…This is because the SSB carries out and functions in monitoring and reviewing banking activities as a whole including reviewing products, services, contracts, preparing guidelines for sharia banking governance, and ensuring principles and compliance with regulations in their records. This can also be an added value for these Islamic banks because with the SBB, customer confidence in banking activities will increase [41]. Therefore, customers will entrust their funds to be managed by Islamic banking which has an impact on improving financial performance.…”
Section: Bmentioning
confidence: 99%